INNOVATION MANAGEMENT ON THE WAY TO BUSINESS EXCELLENCE - Slaana Zivanovic\'; Nikola Abramovic\'; Miodrag Zivanovic\'; Sanja Smolovic\' (Agora International Journal of Economical Sciences (AIJES), 2023)
The current conditions of the global economy have caused innovative changes to be the main condition for a good, sustainable, competitive business of the organization. The solution to the problem can be seen in innovation management, of course with information technology. The goal of this work is the development of innovation with practical software solutions through the innovation management process, i.e. increasing business excellence in the organization. Researchers in organizations use original experience in the implementation of developed software solutions in the field of document management and business innovation. In recent times with globalization and the technological revolution, knowledge has become a key resource for the economic growth and development of nations. Accordingly, the improvement of innovation has become a key condition for the sustainable development and competitiveness of organizations on the local and international market. The results of the conducted research are presented through author-developed programs for statistical data processing and for assessing economic sustainability and achieved business excellence (based on the EFQM 2013 methodology).
Keywords: 330